Overall Survival and Renal Function of Patients With Synchronous Bilateral Wilms Tumor Undergoing Surgery at a Single Institution. Issue 4 (October 2015) - Davidoff, Andrew M.; Interiano, Rodrigo B.; Wynn, Lynn; Delos Santos, Noel; Dome, Jeffrey S.; Green, Daniel M.; Brennan, Rachel C.; McCarville, M. Beth; Krasin, Matthew J.; Kieran, Kathleen; Williams, Mark A.
Abstract : Objectives: Wilms tumor is the most common renal cancer in children. Approximately 5% of children with Wilms tumor present with disease in both kidneys. The treatment challenge is to achieve a high cure rate while maintaining long-term renal function. We retrospectively reviewed our institutional experience with nephron sparing surgery (NSS) in patients with synchronous bilateral Wilms tumor (BWT) operated on between 2001 and 2014. Methods: Imaging studies, surgical approach, adjuvant therapy, and pathology reports were reviewed. Outcomes evaluated included surgical complications, tumor recurrence, patient survival, and renal function, as assessed by estimated glomerular filtration rate. Results: A total of 42 patients with BWT were identified: 39 (92.9%) patients underwent bilateral NSS; only 3 patients (7.1%) underwent unilateral nephrectomy with contralateral NSS. Postoperative complications included prolonged urine leak (10), infection (6), intussusception (2), and transient renal insufficiency (1). Three patients required early (within 4 months) repeat of NSS for residual tumor. In the long-term, 7 (16.7%) patients had local tumor recurrence (managed with repeat NSS in 6 and completion nephrectomy in 1) and 3 had an episode of intestinal obstruction requiring surgical intervention. Overall survival was 85.7% (mean follow-up, 4.1 years). Of the 6 patients who died, 5 had diffuse anaplastic histology. All of the patients had an estimated glomerular filtration rate more than 60 mL/min/1.73 m 2 at the last follow-up; no patient developed end-stage renal disease. Conclusions: In patients with synchronous, BWT, bilateral NSS is safe and almost always feasible, thereby preserving maximal renal parenchyma. With this approach, survival was excellent, as was maintenance of the renal function.